Practical software measurement. Objective information for decision makers : J. McGary, D. Card, C. Jones, B. Layman, W. Clark, J. Dean, F. Hall Addison-Wesley 2002, 2002 - Ramón, Hugo Dionisio (2003)
The authors present the Measurement Information Model and the Measurement Process Model, as well as guidelines based on their experience in order to apply these models to specific projects.